Prospective mathematics teachers’ metaphors for mathematics, teaching, and the teacher’s role - Portaankorva-Koivisto, Päivi (NOMAD Nordic Studies in Mathematics Education, 2012)
This study sheds light on Finnish preservice mathematics teachers’ (n = 16) views of mathematics, teaching, and the teacher’s role. Data was gathered via metaphors at three time points during teacher students’ pedagogical studies, in academic year 2011–2012. The analysis was conducted inductively, but based on categories found in previous studies. The results indicated that prospective mathematics teachers’ metaphors for mathematics mostly involved picturing the self-existent quality of mathematics. Their metaphors for teaching referred to the ups and downs in teaching, and their metaphors for the teacher’s role were involved with the characteristics of the teacher’s personality. One possible explanation for these results centres round mathematics student teachers’ life situations. They have studied mathematics as their major at the department of mathematics for 2–3 years just before they started their pedagogical studies, and they have just experienced their very first and overwhelming lessons as teachers.